Pengenalan Digital Marketing Kepada Santri Pesantren Tahfidz Quran As-Sholah Gunung Sindur Bogor - Dian Megasari; Deanna Durbin Hutagalung; Saprudin (AMMA : Jurnal Pengabdian Masyarakat, 2023)
Community service activities are very important where the service team can share their knowledge with the community. In this case he service team carried out activities at the Tahfidz Quran As-Sholah Islamic boarding school, Gunung Sindur, Bogor. The implementation method is lectures, discussions and training for students, especially for creating content and copywriting from digital marketing. The result of this activities were obtained where the students were able to create content and copywriting to promote something that would be marketed. One of the things to promote something that will be promoted is the Tahfidz Quran As-Sholah Islamic boarding school so that it is increasingly known by the community not only around the Bogor area but throughout Indonesia.